Parent-Child Engagement in Home Learning Activities across Early Childhood: Socio-Demographic Predictors of Change and Associations with Learning Outcomes in the Early Years of School - Walker, Sue; Nicholson, Jan M; Nicholson, J; Walker, S; Hayes, Nicole; Berthelsen, Donna (My University, 2014)
The importance of parent-child engagement in home learning activities in young children’s early development and learning has been well established in international research. Less is known about the home learning environments of Australian children. Nationally and internationally, there is little evidence about the nature of changes across early childhood in the frequency of engagement in home learning activities and the effects on child outcomes as children begin school. Drawing on data from Waves 2, 3 and 4 for the LSAC-B cohort, the current study used latent growth curve modelling to address the following three questions: (1) What is the nature of change in engagement in home learning activities across the ages of 2-3, 4-5 and 6-7 years? (2) What child, maternal and family characteristics are related to change in engagement in home learning activities across the ages of 2-3, 4-5 and 6-7 years? (3) How does change in engagement in home learning activities across the ages of 2-3, 4-5, and 6-7 years relate to children’s language and literacy, and numeracy outcomes on the Peabody Picture Vocabulary Test and Academic Rating Scale at age 6-7 years? Results revealed that level of engagement in home learning activities decreased across the early childhood period. Child gender, maternal ethnicity, education, and family income were significant predictors of the rate of change in engagement. A faster rate of decrease in levels of engagement was also negatively related to children’s language and literacy, and numeracy outcomes at age 6-7 years.
Keywords: Education and Training; Children -- Outcomes; Children -- Early childhood; Children -- School age; Learning, education and training; Education and Training; Children; School age; Early childhood; Outcomes; Learning, education and training